Palliative Care Coordination Interventions for Caregivers of Community-Dwelling Individuals with Dementia: An Integrative Review - Diana Layne; Ayaba Logan; Kathleen Lindell (MDPI AG, 2024)
Alzheimer's disease is a serious illness with a protracted caregiving experience; however, care coordination interventions often lack the inclusion of palliative care. The purpose of this integrative review is to identify and synthesize existing care coordination interventions that include palliative care for individuals with dementia and their caregivers living in community settings. The Whittemore and Knafl framework guided the review, with data analysis guided by the SELFIE framework domains. Study quality was assessed using the Mixed Methods Appraisal Tool, while the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines informed reporting results. Nine care coordination interventions involving family caregivers across eighteen publications were identified. Only a single intervention explicitly mentioned palliative care, while the remaining interventions included traditional palliative care components such as advance care planning, symptom management, and emotional support. Many of the identified interventions lacked theoretical grounding and were studied in non-representative, homogeneous samples. Further research is needed to understand the lived experiences of people with dementia and their caregivers to alleviate care coordination burden.